Male Domination in Drama Scripts It's Crazy Chairil Anwar's Work: A Study of Rw Masculinity Theory. Connell - Herson Kadir; Dewi Malik; Novandawati Masi; Sutrin R. Moha; Narsi Yani; Fitriya Ningsi Hadiu; Sri Indriyani Kadir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research aims to examine male dominance, by focusing on hegemonic masculinity, subordinate masculinity and complete masculinity, in the drama script Already Crazy by Chairil Anwar using the theory of masculinity put forward by RW. Connell. While previous studies on masculinity in Indonesian literature have focused mostly on prose and poetry, the drama genre with its explicit dialogical and performative dimensions has not been explored as a locus for masculinity analysis. This gap is what prompted this research to apply Connell's framework to a canonical Indonesian drama script. This study used a descriptive-analytic qualitative approach. The source of the research data is the drama script Already Crazy by Chairil Anwar, with data in the form of dialogue, monologues and behavioral instructions that are relevant to the research focus. The data collection technique used is the read and record method. Data analysis is carried out by reading drama scripts repeatedly, classifying, describing, analyzing, interpreting and presenting conclusions based on research findings. The research results show that Chairil Anwar's drama script is crazy, representing male dominance through all three categories of Connell's masculinity. For example, hegemonic masculinity is apparent when Mr. Amir's emotional grief is socially interpreted as aberration, rather than as a natural human response. This dominance manifests as a strong tension between the demands of hegemonic masculinity that require men to remain strong, rational, and functional in in mourning and Mr. Amir's psychological reality is vulnerable and depressed. The social community in the manuscript, represented by neighbors, patrol officers and RT administrators, functions as a hegemonic apparatus that carries out social supervision and legitimizes Mr. Amir's marginalization. This research concludes that the play script is Mad Already is not just a story of a widower's grief, but rather a sharp social critique of the destructive impact of the construction of hegemonic masculinity on men's mental health and humanity. These findings contribute to the study of masculinity in Indonesian literary criticism and demonstrate the relevance of Connell's framework for analyzing dramatic texts in non-Western cultural contexts.